African swine fever virus – the possible role of flies and other insects in virus transmission - Fila Mateusz; Woźniakowski Grzegorz (Journal of Veterinary Research, 2020)
African swine fever (ASF) is an acute viral haemorrhagic disease of pigs and wild boars. It presents a serious threat to pig production worldwide, and since 2007, ASF outbreaks have been recorded in the Caucasus, Eastern Europe, and the Baltic States. In 2014, the disease was detected in Poland. ASF is on the list of notifiable diseases of the World Organisation for Animal Health (OIE). Due to the lack of an available vaccine and treatment, the countermeasures against the disease consist in early detection of the virus in the pig population and control of its spread through the elimination of herds affected by disease outbreaks. Knowledge of the potential vectors of the virus and its persistence in the environment is crucial to prevent further disease spread and to understand the new epidemiology for how it compares to the previous experience in Spain gathered in the 1970s and 1980s.